Dyslexia [videorecording] symptoms & solutions - Barton, Susan M. (Bright Solutions for Dyslexia, LLC., 2006)
"If you want to learn more about dyslexia and how it can be overcome, Susan Barton's dynamic, information-packed new DVD is for you. Filmed before a live audience, Susan's lively and captivating presentation provides insights, knowledge, techniques, and inspiration you just can't find anyplace else."--Container.